Relationship between serum lipids and depression: A cross sectional survey among adults in Haryana, India - Rubina Mulchandani; Tanica Lyngdoh; Ria Nangia; Sukriti Singh; Sandeep Grover; JS Thakur (Indian Journal of Psychiatry)
Introduction: Dyslipidemia and mental illnesses are significant contributors to the global noncommunicable disease burden and studies suggest an association between them. Aim: Using data from a noncommunicable disease risk factor survey conducted in Haryana, India, we undertook a secondary data analysis to examine the association between lipids and depressive symptoms. Methods: The survey involved 5,078 participants and followed the World Health Organisation STEPwise approach to NCD risk factor surveillance approach. Biochemical assessments were undertaken in a subset of participants. Lipid markers were measured using wet chemistry methods. Depressive symptoms were assessed using the Patient Health Questionnaire–9. Descriptive statistics were presented for all variables; logistic regression was used for association analyses. Results: The mean age of the study population was 38 years and 55% of them were females. A majority of the participants belonged to a rural background. The mean total cholesterol was 176 mg/dL and approximately 5% of the participants were found to have moderate to severe depression. The association of total cholesterol (odds ratio [OR] 0.99, P = 0.84), LDL-cholesterol (OR = 1.00, P = 0.19), HDL-cholesterol (OR = 0.99, P = .76), and triglycerides (OR 1.00, P = .12) with depressive symptoms was not significant. Conclusion: This study did not find any association between lipids and depressive symptoms. However, further investigations using prospective designs are warranted to understand this relationship and complex interactions with other mediating factors better.